Protocol for Imaging the Same Class IV Neurons at Different Stages of Development. - Shree, S.; Howard, J. (Bio-protocol, 2024)
In this protocol, we focused on analyzing internal branches of Drosophila class IV neurons. These neurons are characterized by their highly branched axons and dendrites and intricately tile the larval body. As Drosophila larvae progress through developmental stages, the dendritic arbors of Class IV neurons undergo notable transformations. As Drosophila larvae develop, their Class IV dendritic arbors grow. In the initial 24 h after egg laying (AEL), the dendrites are smaller than segments. During the subsequent 24 h of the first instar larval stage, dendritic arbors outpace segment growth, achieving tiling. After 48 h, arbors and segments grow concurrently. Epidermal cells near Class IV dendrites expand in proportion to segment growth. This observation suggested that Class IV cells might grow via branch dilation-uniformly elongating branches, akin to Class I cells [1,2]. To understand whether the class IV complex arbor structure is formed by dilation or simply from growing tips, we developed this protocol to introduce a systematic approach for quantitatively assessing the growth dynamics of internal branches. Key features This protocol employs imaging the same neuron over different development times Drosophila embryo and larvae genotype is ;;ppkCD4-tdGFP, which explicitly tags class IV neurons This protocol for the preparation of agar pads to mount and image Drosophila larvae is adapted from Monica Driscoll's method Neurons are imaged without the use of anesthetics and for a short duration of time This technique involves the use of a spinning disk confocal microscope.